Zakat dan Jizyah Sebagai Pengendali Sistem Moneter: Sebuah Kajian Konseptual - Wahyu Nugroho; Syamsuri Syamsuri; Syamsuddin Arif; Dzul Fadli (University of Darussalam Gontor, 2019)
In the history of Islamic civilization, a state guarantees the resource availability through the role it's government, so it can maintain the welfare of its people. The government is free to determine the state’s income policy, which must be fair and not violate sharia. Among the state income policies in Islam are zakat and jizya. Zakat is imposed on Muslims, while jizya is on non-Muslims. History records that both can influence the monetary economy in Muslim countries. Principally, these two are not the same. So, the purpose of this research is to find the concept of zakat and jizya as monetary controllers. This research uses the qualitative method of historical approach, by using past data to understand the events that took place at the moment.The concept of zakat is worship for Muslims to get closer to God and purify the wealth. Meanwhile, jizya is required from non-Muslims as a form of obedience to the government which guarantees their lives in an Islamic state. Moreover, both can affect state's monetary. Because when a Muslim pays zakat, it will increase wealth distribution (aggregate demand), as a result, the recipient becomes prosperous, with the assumption that they will invest. This investment will shift the demand for money (aggregate supply) so that the number of goods and services also increases. Meanwhile, jizya is distributed to government operations including security, so that security can also increase public confidence in carrying out real economic activities, production, distribution, and consumption. Therefore, if zakat and jizya are managed properly, they will keep inflation down. Moreover, it can even eliminate the economic crisis and improve people’s welfare.